Effects of elevated temperatures on electrochemical processes and electrocatalysis and adsorption in the oxygen evolution reaction at alpha and beta lead dioxides. - Ho, Chi Keung (Jimmy). (University of Ottawa (Canada), 1993)
The first part of the thesis is concerned with the problem of temperature dependence of the Tafel slope for various electrochemical processes including the cathodic H$\sb2$ and anodic O$\sb2$ evolution reactions at Au, Pt and Ni in 0.2 N NaOH aqueous solutions at elevated temperatures up to 473 K by means of steady-state polarization experiments. It is found that the commonly assumed representation of the Tafel slope, b, as b = RT/$\beta$F with $\beta$ a constant, often equal to 0.5, is not followed, i.e. $\beta$ is dependent on T. Several examples of this unconventional behaviour of b on temperature are provided in this thesis. The effect of temperature on the surface processes of oxide film formation and reduction in both acid and alkaline aqueous solutions is also examined by means of cyclic voltammetry experiments at temperatures as high as 529 K. In addition to the expected behaviour, such as the higher is the temperature the larger is the rate of reaction, the processes also become more reversible. Experimental examples are provided in this thesis. The second part of the thesis is about the anodic O$\sb2$ evolution reaction at the two "allotropic" forms of lead dioxide, $\alpha$- and $\beta$-PbO$\sb2$ in 1 N HClO$\sb4$ aqueous solutions. The existence of these two forms of PbO$\sb2$ provides a rare opportunity of examining the structural effect in electrocatalysis and kinetics of the O$\sb2$ evolution process. Significant differences between the dimorphs are observed both in the kinetics and the adsorption behaviour of the O and OH intermediates of the reaction. Both potential-relaxation transients, following prior current interruption, and a.c. frequency-response spectroscopy are used in deriving the adsorption behaviour of the reaction intermediates, both H and O/OH species.
Keywords: Chemistry, Analytical.